Antibacterial, Antioxidant, and Phytochemical Screening of Essential Oil - Sangeetha, D. (International Journal of Pharmaceutical & Biological Archive, 2022)
Essential oils (EOs) are liquid mixtures of volatile compounds obtained from aromatic plants. Many EOs have antioxidant properties, and the use of EO as natural antioxidants is a field of growing interest. In the present study was also undertaken with the four different EO, namely, Peppermint oil, Patchouli oil, Frankincense oil, and Ylang Ylang oil were collected from local market. To procure the five pathogens, namely, Staphylococcus aureus, Enterococcus faecalis, Klebsiella pneumoniae, Proteus mirabilis, and Escherichia coli from the Department of Medical Microbiology, RMMCH, Annamalai University. To study the antibacterial activity of four EO against certain pathogenic bacteria by agar well diffusion method. Among the four tested EO ylang ylang EOs exhibited maximum Zone of inhibition against all the tested human pathogens. Based on the maximum antibacterial activity of ylang ylang oil was further subjected to the phytochemical screening and Antioxidant activity.